Implementation of A Decision Making System of Giving Bonus To Employees Using Fuzzy Logic Method - Y Yendrizal (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Each company has its own standards in giving bonuses to outstanding employees in accordance with the company's rules. So we need a system that is able to solve the problem so that the bonus is given according to the performance of each employee. The problem that often occurs today is in the form of a lack of user knowledge in providing bonuses according to employee performance, so that this research can be used as a reference in giving bonuses to each employee according to performance. The solution for giving this bonus uses a decision-making system using Sugeno's Fuzzy Logic. The Sugeno method is to determine the input variable and the output variable which is a firm set, the second step is to change the input variable to a fuzzy set with a fuzzification process, then the third step is to process the fuzzy set data with the minimum method. And the last or fourth step is to change the output into a firm set with a defuzzification process using the centroid method, so that the desired result will be obtained on the output variable. Solving production problems using a comparison of the Sugeno and Mamdani methods. This method uses constants or mathematical functions of the input variables, and in the defuzzification process uses the centralized average method.